Review: Synthesis and Characterization of Dye Combination as Photosensitizer Dye-Sensitized Solar Cell - Rusliani, Prima Fitri; Prima, Eka Cahya (Indonesian Review of Physics, 2024)
The need for energy that continues to increase has led to research processes to create renewable technologies. One of them is manufacturing a Dye-Sensitized Solar Cell with a photosensitizer derived from great natural ingredients, easy to extract and environmentally friendly. Although the resulting efficiency is not as excellent as synthetic materials, combining these natural pigments can expand the absorption area. The efficiency of a combination dye is more significant than a single dye. This review analyses the synthesis process and characterization of the dye combination as a DSSC photosensitizer starting from dye extraction and TiO2 deposition to characterization using various tools. In addition, there are results of research with dye combinations that can be prospects for further study.